Recent advances in environmental biotechnology: role of biosurfactants in remediation of heavy metals (Research, Society and Development, 2022)
Soil contamination by heavy metals is a result of different activities, such as minings, metal smelting, and car battery production. Heavy metals can cause environmental hazards such as contamination of biological systems and the subsoil through the leaching process, and various disturbances and diseases in humans, if they enter the ecosystem, due to their high environmental toxicity and difficult degradability. Non-toxic and biodegradable biological surfactant compounds, also known as biosurfactants, are being used to remediate soils contaminated by heavy metals. The objective of this review is to address the potential application of biosurfactants in the removal of heavy metals and in processes involved in bioremediation. The present study is a narrative review, consisting of a broad analysis of the literature. The searches for the articles used to compose this study were carried out in digital scientific databases, using terms and keywords. This review provides information on biosurfactant application as a promising alternative in heavy metal removal and oil spill bioremediation.